Parametric Studies On Corrosion Behaviour of Cu-Zn-Sn Thin Film - Mohamad, Noor Syahirah Asyikin; Esa, Fahmiruddin; Rosley, Rozainita (Enhanced Knowledge in Sciences and Technology, 2023)
In this study, Cu-Zn-Sn (CZT) thin films were deposited on the carbon substrate using the electrodeposition technique. The effect of deposition time on CZT thin film was investigated which is 15 min, 30 min, and 45 min. The structural, morphological, and chemical composition of the prepared thin films were investigated by X-ray diffraction (XRD) analysis, and scanning electron microscopy equipped with energy-dispersive x-ray spectroscopy (SEM-EDX).  The prepared films were also examined using Electrochemical Impedance Spectroscopy (EIS), Cyclic Voltammetry (CV), and Tafel measurements. It is also can be concluded that deposition times have a strong impact on the appearance and the surface morphology of Cu-Sn-Zn alloy electrodeposits